The IAPT@Flinders Service: adapting the Improving Access to Psychological Therapies model to the emergency department setting in Australia. (June 2014) - Bastiampillai, Tarun; Jones, Gabrielle M; Furber, Gareth; Moreau, Michele; Healey, David; Watson, Julianne; Battersby, Malcolm
Objective: To describe the implementation of an Improving Access to Psychological Therapies (IAPT) service at Flinders Medical Centre emergency department (IAPT@Flinders). IAPT, a population-based model of guided self-help for anxiety and depression delivered mainly by phone, was rolled-out nationally in the UK in 2010. There is a growing body of evidence demonstrating its clinical effectiveness and efficiency that can improve treatment adherence, reduce stigma, remove appointment attendance barriers and improve access for hard-to-reach populations. Conclusions: IAPT@Flinders was the test site for the first IAPT in Australia and also the first IAPT service that was integrated with an emergency department (ED). IAPT@Flinders offers rapid access, low-intensity cognitive behavioural therapy, social prescribing and signposting to clients with adjustment disorders, anxiety and/or depressive symptoms. Successful implementation within an Australian crisis setting has demonstrated that many IAPT structures and protocols are applicable to ED settings and the model can be implemented with fidelity. Adaption required consideration of positioning of the service within the Australian mental health framework; staff qualifications; the referral pathways; and exclusion criteria. It is recommended additional test sites and larger scale trials are conducted to provide further evidence of the applicability of large-scale adoption of the UK IAPT model into Australian ED settings.